Optimization of Online Learning Method Application through Google Classroom in English Education Department of Sulawesi Barat University - Andi Mega Januarti Putri (EDUVELOP, 2020)
Abstract: This research aims to describe the optimization of online learning method through the application of Google Classroom to the students and to find out their responses after using Google Classroom as online learning method. This research had taken participant from English Education Department undergraduate students of 2017 and 2018 which consist of 4 classes that never experienced online learning method before, specifically 101 participants. This research used descriptive qualitative method. Technique of collecting data used in this research is through observation and questionnaire. The result of this research shows that after applying Google Classroom to the students in sharing information or materials, communicating and discussing, submitting assignment, quiz and mid-test, researcher found out that majority of the students in English Education department of Sulawesi Barat University were helped and satisfied with Google Classroom application as online learning method specifically, in assignment submission which were considered simple and paperless. .